Evaluación de ruido laboral y su incidencia en la salud de los trabajadores en los puestos móviles del camal frigorífico municipal de Ambato. Propuesta de un programa para disminuir la afectación a la salud. - Salgado Correa, Diego Fernando (2015)
has been developed in the Camal Refrigerator Municipal Ambato, general objective assess exposure to occupational noise of workers and specific objectives determine the dose of noise, health disorders, and develop a prevention program; for the purpose of reducing the effects on health due to exposure to noise of workers of mobile stations. hypothetical deductive method was used for its implementation; allowing follow a logical process in conducting research in a systematic way. As for the techniques used they were: the interview format INSHT risk assessment of Spain, survey and measuring equipment (dosimeter). The theoretical framework was based on the UNE-ISO-9612 standard, and information regarding the processes taking place in the slaughter in a slaughterhouse. By obtaining data collected through the form of risk assessment INSHT physical risks by noise considered intolerable and important to undertake a risk assessment of mobile stations using measuring equipment (dosimeter 3M Edge) they were prioritized and following the sampling procedure and interpretation of results according to the UNE-ISOP-9612, with the data obtained from this measurement, morbidity statistics and results of surveys of workers proceeds to hypothesis testing using the statistical method Chi square with 95% reliability, enabling accept the alternative hypothesis which states that the level of exposure to occupational noise mobile posts camal refrigerators city of Ambato leads to damages of the health of workers, and it is important to pose a program to decrease the effects on health associated with noise. After the obtained measurement analysis concludes that the dose for the post of collector work legs and heads is 1.55, likewise for the post of inspector quality work dose is 1.01 which indicates that it is high, such a proposal is issued reason to minimize the effect on the physical health risk associated noise which disclosed preventive measures both at the source, transmission medium and worker.